Antioxidant capacity and characteristics of theaflavin catechins and ginger freeze-dried extract as affected by extraction techniques. Issue 1 (1st January 2021) - Imran, Ali; Arshad, Muhammad Umair; Sherwani, Hafsah; Shabir Ahmad, Rabia; Arshad, Muhammad Sajid; Saeed, Farhan; Hussain, Ghulam; Afzaal, Muhammad; Imran, Muhammad; Naeem, Usman; Ikram, Ali; Anjum, Faqir M.
ABSTRACT: The aim of current research was to determine the effect of different extraction techniques on the antioxidant capacity of green tea, black tea and ginger polyphenols. Initially, the raw materials were subjected to compositional analysis. Afterward, the bioactive moieties from all the samples were extracted through ultrasound and conventional solvent extraction method using different solvents (i.e. ethanol, methanol and water). Furthermore, the functional ingredients, namely, catechins and theaflavins were isolated by solvent partition method from green and black tea, respectively. In addition, the extracts and isolates were analyzed for their total phenolic and antioxidant profile using various spectrophotometric assays. For the quantification of theaflavins and catechins, a reverse phase HPLC system was used. Results showed that ultrasound ( P > .005) proved more effectual for the extraction and isolation of polyphenols (757.33 mg/100 g GAE) from the tested materials among the other extraction techniques (741.66 mg/100 g GAE). Likewise, green tea showed better performance than the rest and in solvents ethanol performed better as compared to their counter parts. Similarly, the isolates showed higher antioxidant potential as compared to their extracts and order of effectiveness was catechins > theaflavins > Ginger freeze dried extract (GFDE).